Movimento sindical urbano na Paraíba: organização, lutas por direitos e repressão aos trabalhadores (1958-1964) - Silva, Paula Tamyres Veríssimo da (2021)
This Dissertation analyzes the performance of the urban trade union movement in Paraíba between the years 1958 and 1964, a context of articulation and effervescence of the struggles that were being waged by sectors of the Brazilian working class, which were dismantled due to the intensification of repressive practices with the enactment of Civil-military coup in 1964. Thus, we point to the understanding that this was a class coup, in which the disarticulation of the working class was constituted as the main target of the political proposal of the civil, business and military elites involved in that process. To do so, we seek to reflect, through union action, the various mobilizations of workers that marked the end of the democratic period, the strategies used by them when resorting to the Labor Court, as well as the strong repression that befell these organizations, with impeachments union mandates, interventions, arrests and denunciations, especially to their main leaders. With the Social History of Labor as a theoretical and methodological perspective, the sources used for this research were the main newspapers in Paraíba in circulation at the time, union actions in the Labor Court, memoirs written by union members working in the period, amnesty processes in unionized workers, Military Police Inquiries and oral statements. These last three sources are part of the collection organized by the Truth and Preservation of Memory of the State of Paraíba Commission. This dissertation is part of the History and Regionalities research line and aims to promote discussions about workers in Paraíba and their class organizations.